Cytomegalovirus-Specific T Cell Epitope Recognition in Congenital Cytomegalovirus Mother-Infant Pairs - Materne, Emma C.; Lilleri, Daniele; Garofoli, Francesca; Lombardi, Giuseppina; Furione, Milena; Zavattoni, Maurizio; Gibson, Laura (Frontiers in Immunology, 2020)
Congenital cytomegalovirus (cCMV) infection is the most common infection acquired before birth and from which about 20% of infants develop permanent neurodevelopmental effects regardless of presence or absence of symptoms at birth. Viral escape from host immune control may be a mechanism of CMV transmission and infant disease severity. We hypothesized that longitudinal CD8 T cell responses restricted by shared HLA alleles would show a pattern consistent with maternal loss (by viral escape) and infant gain (by viral reversion to wildtype) of CMV epitope recognition. The study population consisted of 6 women with primary CMV infection during pregnancy and their infants with cCMV infection. CMV UL83 and UL123 peptides with known or predicted restriction by maternal MHC class I alleles were identified, and a subset was selected for testing based on several criteria. Maternal or infant cells were stimulated with CMV peptides in the IFN-γ ELISpot assay. Overall, 14 of 24 (58%; 8 UL83 and 6 UL123) peptides recognized by mother-infant pairs were not previously reported as CD8 T cell epitopes. Of three pairs with longitudinal samples, one showed maternal loss and infant gain of responses to a CMV epitope restricted by a shared HLA allele. CD8 T cell responses to multiple novel CMV epitopes were identified, and the hypothesized pattern of CMV immune escape was observed in one mother-infant pair. Our study emphasizes that CMV escape could operate within the maternal-fetal system and provides rationale for future studies of this potential mechanism of CMV transmission during pregnancy or clinical outcomes of infants with cCMV infection.